Influence of acute mental stress on blood pressure, heart rate and heart rate variability in male medical students: An experimental study from tertiary care hospital, Nepal - Pandey, Karishma Rajbhandari; Khadka, Rita; Panday, Dipesh Raj; Agrawal, Kopila; Paudel, Bishnu Hari (Journal of Biomedical Sciences, 2020)
Background: Medical students experience immense mental stress while understanding and retaining new terms, drug names and mechanisms and eventually generating a concept. Such stress, in long run, may affect their cardiovascular health. This can be assessed by heart rate variability, a reliable non-penetrating tool to determine the cardiac autonomic tone. Material and methods: Thirty healthy young male medical students of BPKIHS, Nepal of age 21.03 ± 1.73 years, and BMI 20.83 ± 2.07 kg/m2 were recruited for the present study. Their resting BP, HR, RR, and short-term heart rate variability (HRV) were recorded in sitting position. Each subject was given a mental stress for 5 min. Their BP, HR, and RR were recorded at 5th min of mental stress. HRV of 5 min was also recorded simultaneously during mental stress. Results: Mental stress increased SBP (p=0.001), DBP (p= 0.001), PR (p= 0.005) and RR (p= 0.042) in young male medical students. Time domain measures of HRV viz; RMSSD (p= 0.001), NN50 (p= 0.001) and PNN50 (p=0.001), which are markers of parasympathetic activity, were significantly decreased during mental stress. Conclusion: Acute mental stress increases BP and HR by withdrawing parasympathetic nervous control in young, healthy male medical students.